2015
DOI: 10.1039/c5ta06108c
|View full text |Cite
|
Sign up to set email alerts
|

Design of an active and durable catalyst for oxygen reduction reactions using encapsulated Cu with N-doped carbon shells (Cu@N-C) activated by CO2treatment

Abstract: Cu@N-C with the Cu particles encapsulated in N-doped carbon shells, which was activated by CO2 treatment, is an excellent electrocatalyst for the oxygen reduction reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
68
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(70 citation statements)
references
References 31 publications
2
68
0
Order By: Relevance
“…The ORR Tafel slope measured for Cu(15%)‐MFC 60 is 82 mV dec −1 , which is slightly higher than the Tafel slope determined for Pt (66 mV dec −1 ) (Figure S8a,b, Supporting Information). To further support the reported values, a similar trend in the ORR activity for copper supported/loaded carbon‐based catalysts has also been observed in the previous reports …”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…The ORR Tafel slope measured for Cu(15%)‐MFC 60 is 82 mV dec −1 , which is slightly higher than the Tafel slope determined for Pt (66 mV dec −1 ) (Figure S8a,b, Supporting Information). To further support the reported values, a similar trend in the ORR activity for copper supported/loaded carbon‐based catalysts has also been observed in the previous reports …”
Section: Resultssupporting
confidence: 89%
“…State‐of‐the‐art ORR electrocatalyst studies have been reported on the development of catalysts utilizing Cu nanostructures into various forms of carbon such as nitrogen‐doped onion‐like graphite nanoshells, n‐doped carbon shells, pyrolytic nitrogen doped carbon, nitrogen codoped graphene, nitrogen doped hierarchical porous carbon, phosphorous doped hierarchically porous carbon, Ketjenblack carbon, zeolitic imidazole derived carbon frame work, and N‐enriched mesoporous carbon . Despite the different synthetic approaches and forms of nanocarbons utilized for the incorporation of Cu NPs, the ORR activity of these catalysts have been attributed to the chemical state of Cu (interior), Cu (surface), and Cu (edge), synergistic contribution from pyridinic N, the hierarchical porous structure and enhanced electrical conductivity tuned by the dopants, higher density of the Cu@Px active sites, facilitation of charge transfer from the inner Cu NPs to the outer N‐doped C shells and favorable electronic interactions with adsorbates in the ORR .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the use of a nonprecious metal encased in a carbon material as an ORR catalyst has gained intense attention not only because of its low cost and comparable catalytic activity to the Pt‐based catalyst but also because of its long‐term durability under acidic conditions . In this kind of catalyst, the outer graphitic layer protects the inner core against corrosion in the acid environment and the inner particles activate the graphitic carbon layer toward the ORR .…”
Section: Introductionmentioning
confidence: 99%
“…Recently,t he use of an onprecious metal encased in a carbon materiala sa nO RR catalysth as gained intense attention not only because of its low cost and comparable catalytic activity to the Pt-basedc atalystb ut also because of itsl ongterm durability under acidic conditions. [14][15][16][17] In this kind of catalyst, the outerg raphitic layer protects the inner core against corrosion in the acide nvironmenta nd the inner particlesa ctivate the graphitic carbonlayer toward the ORR. [18] For instance, Fe nanoparticles encapsulatedi nc arbon shells, [14] Fe-containing compounds encasedi nN -doped graphitic layers, [19] and uniform Fe 3 Cn anoparticles encased by graphitic layers have been synthesized and demonstrated to possess ah igh ORR activity and stability in acid.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, using first-principles density functional theory calculations, 24,25 we have elucidated the role of three-dimensional transition metals (Ni, Co and Cu) in supporting N-doped carbon layers (N-C/M) in ORR catalysis. Cu@N-C shows a much better ORR activity (with an onset potential (E onset ) of 0.94 V and a half-wave potential (E 1/2 ) of 0.83 V vs a reversible hydrogen electrode (RHE)) than pure Cu metal and N-C, thus suggesting that the Cu core substantially influences the electronic structure of N-C shells.…”
Section: Introductionmentioning
confidence: 99%